The antimetastatic breast cancer activity of the viral protein‐derived peptide vCPP2319 as revealed by cellular biomechanics - Oliveira, Filipa (2021)
© 2021 The Authors. The FEBS Journal published by John Wiley & Sons Ltd on behalf of Federation of European Biochemical Societies. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.